Analisis Validitas Materi Uji Multiple Choise Question dengan Learning Objectives Blok Endokrin - Irma Suswati (Universitas Muhammadiyah Malang, 2011)
The evaluation of block learning process uses multiple choice questions (MCQ). The MCQ graduation percentage is very lowon some blocks, especially on the Block IKD-I and Endocrine. The items used have not been tested on their validity and reliability. The purpose of this studys to determine the validity of MCQ test materials with the learning objectives of the Endocrine learning system. The research design uses observational analytical, measured by the MCQ on the difficulty level, the index of the discrimination power and the validity - reliability with alpha coefficient of KR-20 clan. The result MCQ-1 Block Endocrine shows the average value of 51, witn 38.8% completion percentage. Based on the difficulty level, 10.8% belongs to simple questions, 70.3% belongs to medium questions, 18.9% belongs to difficult questions, 27% belongs to goodquestions, 14.9% belongs to good questions but need improvement, and 58.1% belongs to poor that need to be repaired questions. While the valid and reliable items are 62.2% and the invalid and unreliable items are 37.8%. The results showed only a small number of items (25.7%) Endocrine MCQ-I test is valid, reliable, having good difficulty level and was well received. Key words: validity, reliability, questions, MCQ